2007
DOI: 10.1242/jcs.03378
|View full text |Cite
|
Sign up to set email alerts
|

Tau impacts on growth-factor-stimulated actin remodeling

Abstract: The microtubule-associated protein tau interacts with the SH3 domain of non-receptor Src family protein tyrosine kinases. A potential consequence of the SH3 interaction is the upregulation of tyrosine kinase activity. Here we investigated the activation of Src or Fyn by tau, both in vitro and in vivo. Tau increased the kinase activity in in vitro assays and in transfected COS7 cells. In plateletderived growth factor (PDGF)-stimulated fibroblasts, tau appeared to prime Src for activation following PDGF stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
66
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 68 publications
(41 reference statements)
6
66
0
Order By: Relevance
“…Tau can also induce alterations in the actin cytoskeleton, resulting in subsequent neurodegeneration; this is potentiated by A␤ (26). Furthermore, tau has been reported to enhance the kinase activity of fyn in tau-mediated actin rearrangement (27). Taken together, fyn and tau may act in concert to link external A␤ accumulation to cytoskeletal dysregulation and our observations reported here are consistent with this occurring in lipid rafts.…”
Section: Discussionsupporting
confidence: 87%
“…Tau can also induce alterations in the actin cytoskeleton, resulting in subsequent neurodegeneration; this is potentiated by A␤ (26). Furthermore, tau has been reported to enhance the kinase activity of fyn in tau-mediated actin rearrangement (27). Taken together, fyn and tau may act in concert to link external A␤ accumulation to cytoskeletal dysregulation and our observations reported here are consistent with this occurring in lipid rafts.…”
Section: Discussionsupporting
confidence: 87%
“…Because process initiation in Tau-depleted cell lines could not be restored by providing a microtubule stabilizing agent, these findings suggested that a Tau function other than microtubule stabilization was involved in neurite initiation. This was further investigated by testing a phosphomimetic Tau mutant, S262D/S356D, which has a significantly reduced affinity for microtubules both in vitro and in cells (29,(32)(33)(34) (supplemental Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids expressing the 0N3R human Tau mutants S262D/S356D and T231D/S235D have been previously described (29).…”
Section: Methodsmentioning
confidence: 99%
“…Third, tau can enter into reactions other than aggregation, including binding reactions with the SH3 domains of various signal transduction enzymes [56], with other microtubule associated proteins [1], and with the active sites of proteases leading to tau fragmentation [2,48]. These interactions can generate toxicity unrelated to aggregation and therefore complicate interpretation of modeling studies.…”
Section: Complexities Of the Tau Systemmentioning
confidence: 99%